(untitled) - Uyless Black (New York, 1994)
The book provides the latest information on all facets of the Transmission Control Protocol/Internet Protocol and the many protocols that operate within these two standards. Throughout, the book provides invaluable problem-solving guidance, and shows how different vendors vary in their implementation of TCP/IP
Keywords: computer network protocols,tcp/ip ( computer network protocal )